Conflict in Tourism: Parasnath - Bijay Kumar Das; Arpita Srivastava; Avi Kush; Khushbu Kumari (Journal of Social Responsibility, Tourism and Hospitality, 2023)
Land is precious, scarce and limited. It represents territoriality or the extents of anyone’s power. The conflict among individuals and among neighboring nations is because of the land dispute. Parasnath hills are in Giridih district of Jharkhand state in India. The Jain community had built temples and tonks on the hills and is among the most pious pilgrimage sites for them. The hills are Wildlife Sanctuaries’, and a tourism development proposal was in pipeline. The Jain community opposed the move citing the reason of their religious reservations. Jain community refrain from liquor and are pure vegetarian for their food choice. Meanwhile the aboriginal community (Adivasis) too claimed over the hills of Parasnath. This paper examines the triangular conflict on the hills of Parasnath and suggests the measures for conflict resolution.